Greenhouse Gas Inventories Dealing With Uncertainty - Jonas, Matthias; Nahorski, Zbigniew; Nilsson, Sten.; Whiter, Thomas; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The assessment of greenhouse gases emitted to and removed from the atmosphere is high on the international political and scientific agendas. Growing international concern and cooperation regarding the climate change problem have increased the need for policy-oriented solutions to the issue of uncertainty in, and related to, inventories of greenhouse gas (GHG) emissions. The approaches to addressing uncertainty discussed here reflect attempts to improve national inventories, not only for their own sake but also from a wider, systems analytical perspective $1 (Ba perspective that seeks to strengthen the usefulness of national inventories under a compliance and/or global monitoring and reporting framework. These approaches demonstrate the benefits of including inventory uncertainty in policy analyses. The authors of the contributed papers show that considering uncertainty helps avoid situations that can, for example, create a false sense of certainty or lead to invalid views of subsystems. This may eventually prevent related errors from showing up in analyses. However, considering uncertainty does not come for free. Proper treatment of uncertainty is costly and demanding because it forces us to make the step from (3z(Bsimple to complex(3y (Band only then to discuss potential simplifications. Finally, comprehensive treatment of uncertainty does not offer policymakers quick and easy solutions.s
Benefits of dealing with uncertainty in greenhouse gas inventories: introduction -- Statistical dependence in input data of national greenhouse gas inventories: effects on the overall inventory uncertainty -- Uncertainty analysis for estimation of landfill emissions and data sensitivity for the input variation -- Toward Bayesian uncertainty quantification for forestry models used in the United Kingdom Greenhouse Gas Inventory for land use, land use change, and forestry -- Atmospheric inversions for estimating CO2 fluxes: methods and perspectives -- European CO2 fluxes from atmospheric inversions using regional and global transport models -- Remotely sensed soil moisture integration in an ecosystem carbon flux model. The spatial implication -- Can the uncertainty of full carbon accounting of forest ecosystems be made acceptable to policymakers? -- Terrestrial full carbon account for Russia: revised uncertainty estimates and their role in a bottom-up/top-down accounting exercise -- Comparison of preparatory signal analysis techniques for consideration in the (post-)Kyoto policy process -- Verification of compliance with GHG emission targets: annex B countries -- Spatial GHG inventory at the regional level: accounting for uncertainty -- Quantitative quality assessment of the greenhouse gas inventory for agriculture in Europe -- A statistical model for spatial inventory data: a case study of N2O emissions in municipalities of southern Norway -- Carbon emission trading and carbon taxes under uncertainties -- CO2 emission trading model with trading prices -- Compliance and emission trading rules for asymmetric emission uncertainty estimates -- The impact of uncertain emission trading markets on interactive resource planning processes and international emission trading experiments.
Keywords: Environmental sciences; Climatic changes; Environment; Climate Change; Fossil Fuels (incl. Carbon Capture).; Environmental Monitoring/Analysis.